Keputusan Bertahan Perajin Ukir Mulyoharjo Jepara dalam Tekanan Sosial Ekonomi - Mushoffa, Muhammad Zaki; Trinugraha, Yosafat Hermawan (Riwayat: Educational Journal of History and Humanities, 2025)
This study examines the persistence of woodcarvers in Mulyoharjo, Jepara, in sustaining their profession amid pressures from modernization, minimalist market trends, and declining youth interest. Employing a qualitative case study approach, data were collected through semi-structured interviews with woodcarvers, participant observations, and document analysis. Guided by Colemans rational choice theory, the findings reveal that persistence stems from a calculated response to social, economic, and cultural conditions. Cultural norms, such as pride in Jeparas carving heritage, alongside adaptive strategies like social networks and work autonomy, drive their decisions. Despite unstable markets and limited institutional support, woodcarvers rely on traditional skills and community ties to navigate challenges. The study concludes that their persistence reflects bounded rationality, shaped by cultural values and structural constraints. Sustaining the woodcarving profession requires context-sensitive support that prioritizes artisans perspectives and real-world needs